ABO Blood Type and Urinary Bladder Cancer: Phenotype, Genotype, Allelic Association with a Clinical or Histological Stage and Recurrence Rate - Ivan Milas; Željko Kaštelan; Jószef Petrik; Jasna Bingulac-Popović; Bojan Čikić; Andrej Šribar; Irena Jukić (Global Medical Genetics)
Background Previous research on connection between the ABO blood group and bladder cancer has been based on determining the ABO phenotype. This specific research is extended to the molecular level, providing more information about particular ABO alleles.